Real-Time Detection of Vehicle Speed Based on Video Image - Cheng, Genyuan; Guo, Yubin; Cheng, Xiaochun; Wang, Dongliang; Zhao, Jiandong (International Conference on Measuring Technology and Mechatronics Automation (Print), 2020)
With the continuous development and improvement of Intelligent Transportation System, more and more attention has been paid to the real-time and accurate speed information detection. Video vehicle speed detection based on machine vision has attracted the attention of the researchers due to its practical convenience and other advantages. In this paper, we propose a target tracking method based on video image feature matching vehicle to simplify the algorithm complexity and obtain high accuracy. The background subtraction method based on KNN algorithm is used to identify vehicle targets and obtain good initial vehicle characteristics. Experimental results show that the method has high real-time and the relative error of vehicle speed detection can be controlled at about 5%.